Analysis of Factors Affecting Operational Performance of Logistics Companies in Indonesia - Ilmi, Bahrul; Sabitah, Sabitah (Inspiring Law Journal, 2024)
Companies are always required to have good performance. Performance in English is also called job performance or actual performance, which is the level of success of the company in achieving its goals. The study focused on shipping, receiving, storing, and transportation activities in logistics activities. The instrument used in this study was a questionnaire. This questionnaire was distributed to 37 logistics service companies as a unit of analysis. Data processing consisted of reliability testing using the Cronbach's alpha method, and validity testing using the analysis corrected item total correlations method. Furthermore, factor analysis was carried out using exploratory factor analysis (EFA). The results of the study showed that there were 4 groups of business process factors and 5 groups of SCM factors. The groups that emerged were the result of factor reduction carried out